2020
DOI: 10.1371/journal.pone.0229942
|View full text |Cite
|
Sign up to set email alerts
|

Using consumer-wearable technology for remote assessment of physiological response to stress in the naturalistic environment

Abstract: Psychosocial stress is a major risk factor for morbidity and mortality related to a wide range of health conditions and has a significant negative impact on public health. Quantifying exposure to stress in the naturalistic environment can help to better understand its health effects and identify strategies for timely intervention. The objective of the current project was to develop and test the infrastructure and methods necessary for using wearable technology to quantify individual response to stressful situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 54 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…A total of 15 studies were identified for inclusion in this review based on the search term “stress”. Similar to anxiety, the use of cardiac metrics, namely heart rate and heart rate variability, were the predominant physiological markers of stress detection in 10 of the 15 studies which detected stress [ 9 , 12 , 14 , 17 , 18 , 20 , 22 , 23 , 26 , 28 ]. It has been reported that altered HRV measurements are related to ANS dysregulation associated with many cardiovascular diseases including cardiac ischemia, myocardial infarction and heart failure, diabetes, and obesity, as well as mental health conditions including anxiety and depression [ 9 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 15 studies were identified for inclusion in this review based on the search term “stress”. Similar to anxiety, the use of cardiac metrics, namely heart rate and heart rate variability, were the predominant physiological markers of stress detection in 10 of the 15 studies which detected stress [ 9 , 12 , 14 , 17 , 18 , 20 , 22 , 23 , 26 , 28 ]. It has been reported that altered HRV measurements are related to ANS dysregulation associated with many cardiovascular diseases including cardiac ischemia, myocardial infarction and heart failure, diabetes, and obesity, as well as mental health conditions including anxiety and depression [ 9 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies that only examined HR [ 20 , 22 ] it was found that there was a significant difference between genders, with females having significantly higher average HR than males when exposed to occupational stress, when measured using an Apple Watch (Series 1, Apple Inc., Cupertino, CA, USA) [ 20 ]. Interestingly, Lucas et al (2019) also commented that baseline cardiovascular fitness, determined by survey, had no significant impact on HR, which is the inverse of what is physiologically expected [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study using smart-watches to deliver and monitor a breathing intervention, for example, reported one sixth fewer stress instances among participants randomly assigned to the smart-watches group compared to the waiting list group (Smith et al, 2020). Smart-watches and associated health apps allow users to share information on their current levels of activity, physical exercise, and sleep (Pakhomov et al, 2020). Therefore, the same indicators may be used to deliver or assess intervention effects.…”
Section: Collect Demographic Datamentioning
confidence: 99%